Energy Market Integration in Northeast Region of India: Efficiencies, Vulnerabilities and Strategic Implications for Asia. Issue 1 (April 2020) - Anbumozhi, Venkatachalam; Kutani, Ichiro; Singh, Bhupendra Kumar
Abstract: Energy is a common thread that connects multiple economic domains of countries and sub-regions in Asia. In the drive to trigger and consolidate energy market integration, the North Eastern Region (NER) of India offers great potential as electricity trading hub. This article analyses multiple potentials of energy markers of NER with neighbouring countries through cross-border trade. Supply and demand analysis under different connectivity scenarios shows that not only the eight states of NER of India may be able to fully utilise the economic benefits of energy market integration, but also the neighbouring countries like Bangladesh, Bhutan and Myanmar should keep their carbon emissions in check by importing reliable cost effective energy sources. However, lack of infrastructure for the transfer of power to a common transmission system increases the vulnerability of energy market integration. Given the region's diverse hydro-geography and wide range of clean energy portfolios, energy market integration perspective offers a way forward for strategic energy security planning and climate mitigation strategy for NER and neighbouring Asian countries.